2012
DOI: 10.1080/09603123.2011.634387
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of childhood asthma in Northern Israel is linked to air pollution by particulate matter: evidence from GIS analysis and Bayesian Model Averaging

Abstract: The medical records of 3922 school children residing in the Greater Haifa Metropolitan Area in Northern Israel were analyzed. Individual exposure to ambient air pollution (SO(2) and PM(10)) for each child was estimated using Geographic Information Systems tools. Factors affecting childhood asthma risk were then investigated using logistic regression and the more recently developed Bayesian Model Averaging (BMA) tools. The analysis reveals that childhood asthma in the study area appears to be significantly asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 69 publications
1
19
0
Order By: Relevance
“…The performed analyses confirmed the associations between asthma prevalence and air pollution published in literature (6,7,25) only in case of Model 3. Surprisingly, there were also associations with land use/land cover, in all three models.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The performed analyses confirmed the associations between asthma prevalence and air pollution published in literature (6,7,25) only in case of Model 3. Surprisingly, there were also associations with land use/land cover, in all three models.…”
Section: Discussionsupporting
confidence: 77%
“…The most often discussed hazard factors are air pollutants emitted from the traffic and industry. There are connections between asthma occurrence and particulate matter less than 10 μm in aerodynamic diameter (PM 10 ) and smaller (5)(6)(7)(8)(9)(10), NO 2 (5,(11)(12)(13)(14) and SO 2 (6). Generally, the quality of the environment is also affected by other parameters like land use and agricultural production (15,16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the precise composition of air pollution varies widely by location, often promoting regionally specific effects on human health. In general, inhaled PM tend to cause airway irritation that can negatively impact respiratory conditions such as asthma (1)(2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
“…Whereas it is generally accepted that air pollution can aggravate existing asthma, it is less clear whether exposure to air pollutants plays a causal role in the development of asthma. Crosssectional studies have found an association between current air pollution levels and asthma prevalence, implying that pollution may increase the risk for developing asthma (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). However, studies that measure the association of air pollution exposures that occur before asthma onset are necessary to evaluate the causality of this association.…”
mentioning
confidence: 99%